Exploring Authentic Assessment of Online EFL Classrooms in a Senior High School - Fitrianingrum, Fifi (RETAIN, 2021)
The objectives of the study are to explore the implementation of authentic assessment, particularly performance assessment, portfolio assessment, and project assessment during online learning, the problems or obstacles encountered by both English teachers and the students, and the solutions taken to overcome those problems. The data are obtained by conducting a semi-structured interview with the Vice-Principal of Academic Affairs and Curriculum, two English teachers who teach XI grade and X grade students, and the students of XI and X grades in the academic year 2020/2021 consist of 9 students in total. The results of the study reveal that authentic assessments were implemented only for assessing students’ productive skills, and the teachers applied authentic assessment during online learning and when a hybrid system was run. The teachers gave various types of assignments in the process of implementing authentic assessments, and both English teachers and the students encountered several problems related to the application of authentic assessment and online learning. However, the teachers, as well as the students, could find effective solutions to their problems. Keywords: authentic assessment, English teachers, students, online learning.